What is chemistry? - Atkins, P. W. (Peter William), 1940-, author (Oxford, United Kingdom : Oxford University Press, 2013)
Most people remember chemistry from their schooldays as a subject that was largely incomprehensible, fact-rich but understanding-poor, smelly, and so far removed from the real world of events and pleasures that there seemed little point, except for the most introverted, in coming to terms with its grubby concepts, spells, recipes, and rules. Peter Atkins wants to change all that. In What is Chemistry? he encourages us to look at chemistry anew, through a chemist's eyes, to understand its central concepts and to see how it contributes not only towards our material comfort, but also to human culture --Source other than Library of Congress